Uma tragédia anunciada : a invasão da fronteira oeste do Império do Brasil na Guerra do Paraguai (1850-1870) - Rodrigues, Fabian Diego de Castro (2016)
This work aims to deepen the debate on the Paraguayan War and present new perspectives on the events that happened in Mato Grosso province between 1850 and 1870, considering the politics instability between the Platine countries in this period. Points out that between 1850 and 1864 the leaders of the Mato Grosso province warned the Court of the Empire the western border would not resist, should it happen, any assault of a possible enemy. However, it points out that the Empire was unable to reorganize the defense of the western border. With the advent of sending troops to Paraguay Paraguay 's lower region, the current western region of Mato Grosso do Sul state, the province of Mato Grosso was unable to secure the territorial sovereignty of the Empire remained occupied almost the entire war.